2021
DOI: 10.4103/ijo.ijo_2617_20
|View full text |Cite
|
Sign up to set email alerts
|

Resuming eye bank services during the COVID-19 pandemic

Abstract: Purpose: The aim of this study was to formulate a methodological approach for resuming eye bank services during COVID-19 pandemic. Methods: Eye bank operations were temporarily halted in March after the government-mandated “Lockdown” in response to COVID-19 pandemic. Before restarting eye bank operations in May, we studied sources of exposure, performed risk assessment, instituted additional process validations and redefined the Standard Operating Procedures (SOPs) in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Acharya et al . [ 10 ] have published a good framework for comprehensive operating protocols for restarting eye bank services. Though 82% of the eye banks in our survey provided additional training to staff before resuming operations, the 18% gap does bother us.…”
Section: Discussionmentioning
confidence: 99%
“…Acharya et al . [ 10 ] have published a good framework for comprehensive operating protocols for restarting eye bank services. Though 82% of the eye banks in our survey provided additional training to staff before resuming operations, the 18% gap does bother us.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Similar situations were reported virtually in the entire globe, including India, Germany and Canada. 24 , 28 , 29 Both AlShaker et al and Acharya et al reported Eye Bank Staff to have been trained to the appropriate and constant use of personal protective equipment, and exposure risk analysis strategies (e.g., questionnaires, body temperature check, nasopharyngeal swab, etc.) to have been implemented to minimize the risk of in bank SARS-CoV-2 transmission.…”
Section: Covid-19 and Eye Bankingmentioning
confidence: 99%
“…Standardized operating procedures (SOP) needed to be revised, too. An increasing number of checkpoints were added to avoid unnoticed potential exposure to SARS-CoV-2 (e.g., checklist for double-checking donor medical history and a detailed tissue tracker), according to the experience of Acharya et al 29 …”
Section: Covid-19 and Eye Bankingmentioning
confidence: 99%
See 2 more Smart Citations